Correlation of the Covid-19 Pandemic and Act of Violence against Children in the Family - Sukiati; Sumariati (Budapest International Research and Critics University, 2021)
The COVID-19 pandemic has had various impacts on people's lives. One of the impacts of the COVID-19 pandemic is believed to be the increase in acts of violence against children in families. The research will explore the factors that have made the COVID-19 pandemic a trigger for increased acts of violence against children in families in Indonesia. By using qualitative research this research was conducted from 2020-2022. Data collected by interview and observation. The participants involved in this research were parents, children, non-governmental organizations (NGOs) and the community. The results of this study indicate that the COVID-19 pandemic can trigger factors of violence against children in the family. These factors include factors of religious teachings, economics, divorce, psychology, education, and social. This study concludes that there is a strong correlation between the COVID-19 pandemic as a trigger and factors for acts of violence against children in the family. By looking at the results of the research above, it is necessary to pay attention to the government and society from various aspects to prevent and minimize violence against children in the family, especially during difficult times such as disasters or pandemics.